A Independent Sample T Test Analysis: Case Study of Bank Mandiri with BNI 46 - Sasono, Heri (Jurnal Keuangan dan Perbankan, 2024)
Currently there are four government-owned banks, namely; Bank Mandiri, Bank Rakyat Indonesia (BRI), Bank Tabungan Negara (BTN) and Bank Nasional Indonesia (BNI) 46. Of these four banks it can be said to have quite good performancej, proven to have provided dividends to the State treasury over the last few years.This research wants to see the difference in the average performance of the two government-owned banks, namely between Bank Mandiri and Bank Negara Indonesia over the last 10 years from 2014 to 2023.Research analysis of normality test, homogeneity test and independent sample t test using SPSS software version 26, to analyze the variables ROA, NPL, LDR, BOPO, CAR, NIM and ROE. The research shows that only the financial ratios Return on Equity (ROE) and Loan Deposit Ratio (LDR) have significant differences, while the ratios of Return on Assets (ROA), Net Interest Margin (NIM), Operational Costs to Operating Income (BOPO) and Net Performing Loans (NPL) and Capital Aduqucy Ratio (CAR), did not have a significant difference between Bank Mandiri and Bank Nasional Indonesia (BNI) 46, for 10 years, starting from 2014 until 2014. 2023.